2022
DOI: 10.3390/brainsci12020269
|View full text |Cite
|
Sign up to set email alerts
|

An EEG-Based Investigation of the Effect of Perceived Observation on Visual Memory in Virtual Environments

Abstract: The presence of external observers has been shown to affect performance on cognitive tasks, but the parameters of this impact for different types of tasks and the underlying neural dynamics are less understood. The current study examined the behavioral and brain activity effects of perceived observation on participants’ visual working memory (VWM) in a virtual reality (VR) classroom setting, using the task format as a moderating variable. Participants (n = 21) were equipped with a 57-channel EEG cap, and neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Overall, it was found that investigation of stress levels improves the quality of academic classes [45,129]. Students' stress levels increase before examinations and during timed exams [60,71,130], and high levels of stress are correlated to poorer evaluation performance and psychological health problems [77,83]. Other analyzed physiological constructs include motivation [87], flow state [62], concentration [68], and sustained attention [118], where an increase in all of them correlates to improved educational interventions and allows the possibility of implementation of e-learning platforms through BCIs or Augmented Reality (AR) systems [62,68].…”
Section: Discussionmentioning
confidence: 99%

Wearable Biosensor Technology in Education: A Systematic Review

Hernández-Mustieles,
Lima-Carmona,
Pacheco-Ramírez
et al. 2024
Preprint
“…Overall, it was found that investigation of stress levels improves the quality of academic classes [45,129]. Students' stress levels increase before examinations and during timed exams [60,71,130], and high levels of stress are correlated to poorer evaluation performance and psychological health problems [77,83]. Other analyzed physiological constructs include motivation [87], flow state [62], concentration [68], and sustained attention [118], where an increase in all of them correlates to improved educational interventions and allows the possibility of implementation of e-learning platforms through BCIs or Augmented Reality (AR) systems [62,68].…”
Section: Discussionmentioning
confidence: 99%

Wearable Biosensor Technology in Education: A Systematic Review

Hernández-Mustieles,
Lima-Carmona,
Pacheco-Ramírez
et al. 2024
Preprint
“…Overall, it was found that investigation of stress levels improves the quality of academic classes [ 45 , 121 ]. Students’ stress levels increase before examinations and during timed exams [ 60 , 69 , 124 ], and high levels of stress are correlated with poorer evaluation performance and psychological health problems [ 75 , 81 ]. Other analyzed physiological constructs include motivation [ 85 ], flow state [ 26 ], concentration [ 66 ], and sustained attention [ 113 ], where an increase in all of them correlates to improved educational interventions and allows for the possibility of implementation of e-learning platforms through BCIs or AR systems [ 26 , 66 ].…”
Section: Discussionmentioning
confidence: 99%

Wearable Biosensor Technology in Education: A Systematic Review

Hernández-Mustieles,
Lima-Carmona,
Pacheco-Ramírez
et al. 2024
Sensors
Self Cite
“…For older adults, design factors and intuitive interfaces may be particularly important in promoting the adoption of VR technology and comfort with using it ( Roberts et al, 2019 ; Siriaraya & Ang, 2019 ; Syed-Abdul et al, 2019 ). A topic that has repeatedly emerged in the research literature is the design of avatars and full-body tracking to reflect real-world experiences ( Darfler et al, 2022 ; Kalantari & Neo, 2020 ). Older adults tend to prefer more “realistic engagement” scenarios in VR that reflect ordinary environments and people, rather than “gamified” scenarios that bestow users with superhuman abilities to perform challenging tasks ( Freeman & Maloney, 2021 ; Freeman et al, 2020 ).…”
Section: Prior Research On Vr Use Among Older Adultsmentioning
confidence: 99%